HUBUNGAN KETEPATAN PENGGUNAAN INHALER DENGAN LUNG CAPACITY PADA PENDERITA ASMA - Zekia, Natasya Sri; Hairani Damanik, Siti Rahmalia; Utomo, Wasisto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Asthma is one of the chronic non-communicable disease and often occur repeatedly if it is not being controlled, one of tool used to evaluate lung capacity is spirometry. This research aims to determine correlation between accuracy of the use of inhalers and lung capacity of asthmaâs patients. This research used correlation quantitative research method with Cross Sectional design. Sample method used is purposive sampling with 30 respondents. Measuring instrument in this research is spirometry and width of research is to see accuracy of the use of inhalers. Data analysis used are univariate analysis to see the frequency distribution and bivariate analysis to determine relationship between 2 variables by using Kolmogorov-Smirnov test. Results indicate there is correlation between accuracy of the use of inhalers with lung capacity on asthmaâs patient with p value (0,036) <É (0,05). This research expects every public health center to perform evaluation on accuracy of the use of inhalers and check lung capacity periodically.Keywords: Asthma, Inhalers, Lung Capacity